PENERAPAN MODEL PEMBELAJARAN MURDER (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND REVIEW) DALAM PENGUASAAN KOSAKATA BAHASA MANDARIN SISWA KELAS X SMA ISLAM ATHIRAH MAKASSAR - Noviana Salis; Misnawaty Usman; Muhammad Anwar (Phonologie : Journal of Language and Literature, 2020)
Abstract. The purpose of this research was to find out the application of MURDER learning model in mastery of Chinese vocabulary for 10th Grade students of Athirah Islamic High School 1 Makassar. This type of research is experimental research which consist experimental classes and control classes. Data from this research was obtained by giving the students pre-test and post-test with the material about “Part of Body”. The result of t-test calculation at a significant level of 0.05 obtained the value of t-count = 0,013 which was less than t table 2,120.